2008
DOI: 10.1590/s0100-29452008000200025
|View full text |Cite
|
Sign up to set email alerts
|

Teores de carboidratos em órgãos lenhosos do caquizeiro em clima tropical

Abstract: RESUMO-Nas fruteiras caducifólias, o metabolismo de carboidratos constitui-se no principal mecanismo que garante a sua sobrevivência no período de dormência, estando, também, relacionado ao seu potencial produtivo em safras subseqüentes. Conhecer a forma como a planta utiliza esses carboidratos durante o seu desenvolvimento é um passo importante para o entendimento das suas relações fonte-dreno e para fundamentar algumas práticas de manejo, como a poda e o raleio de frutos. Caracterizar a variação dos teores d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
(11 reference statements)
3
9
0
1
Order By: Relevance
“…However, starch content increased later after 72 days, possibly due to preventing the sprouting of buds of the stored branches, to detriment of the low temperature of the cold conservation storage ( Figure 2B). CORSATO et al (2008) also observed an equation identical to that of the present paper for starch contents in persimmon tree branches over time.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…However, starch content increased later after 72 days, possibly due to preventing the sprouting of buds of the stored branches, to detriment of the low temperature of the cold conservation storage ( Figure 2B). CORSATO et al (2008) also observed an equation identical to that of the present paper for starch contents in persimmon tree branches over time.…”
Section: Resultssupporting
confidence: 88%
“…In figure 2A, it is reported that there was a linear increase in the total soluble sugar contents insofar as the branches remained stored over time. CORSATO et al (2008) reported increased total soluble sugar contents in persimmon tree branches beginning at the end of the dormancy period. Since the persimmon tree branches used in this study were collected precisely during the dormancy period, a rise in the total soluble sugar contents was expected.…”
Section: Resultsmentioning
confidence: 96%
“…Larcher [7] also reports that the intensity of mobilization of carbohydrates influences the branch growth, flowering and fruit production. The results of this study are in agreement with those found by Corsato [29], which evaluated the carbohydrates variation in the root and branch persimmon variety Rama Fort, observed higher total soluble carbohydrates in roots and branches in the months of September and October (spring) due to the air temperature increase.…”
Section: Accumulation and Levels Of Total Carbohydratessupporting
confidence: 93%
“…The same behavior was observed for time 2, when there was an increase of 134.85% in the maximum fertilizer dose in relation to the absence of the product. Similar results were found by Corsato et al (2008), in 'Rama Forte' persimmon plants, which also showed increase in sugar content in the period before flowering.…”
supporting
confidence: 86%